Electrical and deilectric properties of CdWO₄ crystals - Shevchuk, V.N.; Kayun, I.V. (Functional Materials, 2006)
Electrophysical investigations of CdWO₄ crystals have been carried out by thermostimulated polarization and thermoelectret state depolarization in interrelation with temperature dependences 290-550 K of DC conductivity and permittivity at 1 kHz frequency. The depolarization currents are correlated with activation of the dipole defect complex reorientation processes (current peaks at 308, 319, 338 and 365 K) and with development of spatially heterogeneous of the volumetric charge which as a result of localization of the current carriers on capture levels (the wide non-elementary intense maximum at 400-550 K). The basic parameters of the main relaxators and conductivity have been estimated. The explanation of the electrical properties and polarization effects are based on the assumed predominance of intrinsic structural defects that may be probably the cadmium and oxygen vacancies and also defect complex based on these vacancies. The experimental data on conductivity do not contradict to small-polaron theory.